The Role of Knowledge Sharing and Behavior in Improving Individual Innovation Capability in Umkm in Gombang Village Indonesia - Adinda Melati; Putri Yuliasari; Anna Suzana; Sandi Nasrudin Wibowo (Dinasti International Journal of Education Management And Social Science, 2025)
This study examines the role of knowledge sharing and behavior in improving individual innovation capability in MSMEs in Gombang Village, Cirebon Regency. Data were obtained from 162 MSMEs using quantitative methods using SEM-PLS. This study revealed that there is a positive and substantial relationship between information sharing and behavior with individual creative potential (R² = 0.840). The results showed that these two factors contributed 84% of the variance in community innovativeness. This study recommends increased collaboration and training support to encourage innovation in the MSME sector.